2014
DOI: 10.1002/ange.201404847
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Luminescent Lanthanide Dimers for Fluoride Sequestering and Sensing

Abstract: Lanthanide complexes (Ln = Eu, Tb, and Yb) that are based on a C 2 -symmetric cyclen scaffold were prepared and characterized. The addition of fluoride anions to aqueous solutions of the complexes resulted in the formation of dinuclear supramolecular compounds in which the anion is confined into the cavity that is formed by the two complexes. The supramolecular assembly process was monitored by UV/ Vis absorption, luminescence, and NMR spectroscopy and high-resolution mass spectrometry. The X-ray crystal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
2
13
1
Order By: Relevance
“…Peaks corresponding to the hydrated complex and the fluoride adduct were found to have very similar diffusion coefficients suggesting that they are of comparable size. This contrasts with the aforementioned C 2 ‐symmetric system studied by Charbonnière and co‐workers, in which intermolecular forces were postulated to induce dimer formation in solution ,…”
Section: Crystal‐field Analysiscontrasting
confidence: 64%
See 2 more Smart Citations
“…Peaks corresponding to the hydrated complex and the fluoride adduct were found to have very similar diffusion coefficients suggesting that they are of comparable size. This contrasts with the aforementioned C 2 ‐symmetric system studied by Charbonnière and co‐workers, in which intermolecular forces were postulated to induce dimer formation in solution ,…”
Section: Crystal‐field Analysiscontrasting
confidence: 64%
“…When the aromatic group is indazole, hydrogen‐bonding interactions stabilise a binuclear system, in which two complexed lanthanide centres are linked by bridging fluoride: in this system, a log K a value of 13.0 was obtained for a 2:1 binding event ,. In a related quinoline‐based system, a 1:1 binding of fluoride with log K a 4.1 (at pH 6) was measured . The affinity of our C 4 ‐symmetric tetrapicolyl complexes for fluoride is comparable to these C 2 ‐symmetric systems.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, the solid‐state 13 C CP/MAS NMR spectrum shows a moderate signal at 90 ppm assigned to C of the CC bond, suggests bonding of the triarylborane node and 4,4′‐diethynylbiphenyl linker (Figure 1). Other peaks ranging from 120–150 ppm can be assigned to the aromatic C atoms of phenyl rings,12a, 16 and the peak at 19 ppm to aliphatic methyl substituents of the phenyl rings 6a. 17 The presence of boron in BMOP was confirmed by X‐ray photoelectron spectroscopy (XPS).…”
Section: Resultsmentioning
confidence: 97%
“…In our quest to design efficient Ln‐based luminescent sensors for anions in solution, we designed the octadentate ligand L, which forms [LnL(H 2 O)]Cl complexes in the presence of LnCl 3 salts (Ln=Eu, Tb, Yb) in water. It was demonstrated that the introduction of fluoride anions into aqueous solutions of the hydrated monomer led to the formation of supramolecular [(LnL) 2 F] + dimers (Scheme ) . Spectroscopic evidence further demonstrated that the formation of the dimer was the result of a positive associative cooperative process .…”
Section: Resultsmentioning
confidence: 99%